Trends in HCV treatment uptake, efficacy and impact on liver fibrosis in the Swiss HIV Cohort Study. (23rd August 2017) - Béguelin, Charles; Suter, Annatina; Bernasconi, Enos; Fehr, Jan; Kovari, Helen; Bucher, Heiner C.; Stoeckle, Marcel; Cavassini, Mathias; Rougemont, Mathieu; Schmid, Patrick; Wandeler, Gilles; Rauch, Andri; et al.
Abstract: Background & Aims: Hepatitis C virus (HCV) therapies with interferon‐free second‐generation direct‐acting antivirals (DAAs) are highly effective and well tolerated. They have the potential to increase treatment eligibility and efficacy in HIV‐infected patients. We assessed the impact of DAAs on treatment uptake and efficacy, as well as its impact on the burden of liver disease in the Swiss HIV Cohort Study (SHCS). Methods: We describe clinical and virological characteristics of patients treated with second‐generation DAAs. We compared treatment incidence, sustained virological response (SVR)12 and liver fibrosis stages between three time periods: period 1, 01/2009‐08/2011 (prior to the availability of DAAs); period 2, 09/2011‐03/2014 (first generation DAAs); period 3, 04/2014‐12/2015 (second generation DAAs). Results: At the beginning of the third period, 876 SHCS participants had a chronic HCV infection of whom 180 (20%) started treatment with a second‐generation DAA. Three‐quarters of them had advanced liver fibrosis (Metavir ≥ F3) of whom 80% were cirrhotics. SVR12 was achieved in 173/180 (96%) patients, three patients died and four experienced a virological failure. Over the three time periods, treatment uptake (4.5/100 py, 5.7/100 py, 22.4/100 py) and efficacy (54%, 70%, 96% SVR12) continuously increased. The proportion of cirrhotic patients with replicating HCV infection in the SHCS declined from 25% at the beginning to 12% at the end of the last period. Conclusions: After the introduction of second‐generation DAAs, we observed an increase in treatment uptake and efficacy which resulted in a significant reduction in the number of cirrhotic patients with a replicating HCV infection in the SHCS.